Non-Neighbor Reduced Randic and Sum-Connectivity Index - G. R. Roshini; S. B. Chandrakala; R. Indira; B. Sooryanarayana (International Journal of Mathematics And its Applications, 2019)
In this article, we have computed the non-neighbor reduced-Randic, sum-connectivity index and multiplicative non-neighbor reduced-Randic, sum-connectivity index for some standard graphs and for corona product of some graphs.